Dynamic HR : Global Applications from IBM - Morris, S. S.; Calamai, R. (2012)
As business leaders increasingly understand the importance of effectively managing a global workforce, attention turns to the human resource (HR) function. But as FIR groups focus largely on best practices, they lose sight of the constantly shifting demands of a global environment that requires next practices. We propose a new Dynamic HR framework that allows HR managers constantly to renew and reintegrate their practices throughout the organization in a way that focuses on flexible entrepreneurship and coordinated networking among dispersed HR managers. Such demands require HR managers who not only are connected with one another across the globe, but also are one step ahead of shifting local and global demands. Using practical examples from IBM, we discuss techniques that might help HR become more dynamic. (C) 2009 Wiley Periodicals, Inc.